Unconformity-Related Rare Earth Element Mineral Potential of Australia - Arianne Ford; Jessica Walsh; Michael Doublier; Antony Burnham; Jonathan Cloutier; Geoff Fraser; Charles Magee; Karol Czarnota (Natural Resources Research, 2026)
Heavy rare earth elements (HREE) are critical for the transition to net zero in addition to being key to manufacturing defense technologies. Unconformity-related rare earth element (REE) deposits represent an important source of HREE, including key elements such as dysprosium (Dy) and terbium (Tb). Given the strategic importance of these critical minerals to the national economy, a national-scale mineral potential assessment has been undertaken to evaluate the geological potential for unconformity-related REE mineral systems in Australia. Leveraging previous research into the formation of unconformity-related REE mineral systems in Australia, a new model for the mineral system has been developed based on an existing mineral systems framework. The deposits form as a result of crustal- to deposit-scale processes that operate under favorable spatial and temporal conditions. This study demonstrates how a mineral system that has uncertainties regarding its formation can be used as the basis for predictive modeling through the novel use of datasets not typically utilized in broad-scale mineral potential assessments. Both a knowledge-driven and data-driven approach have been used to generate national-scale mineral potential maps that reduce the exploration search space for unconformity-related REE mineral systems in Australia by up to 95%. In addition to predicting known mineralized regions, the model also demonstrates high prospectivity in parts of Australia where no unconformity-related REE mineralization has previously been identified, particularly on the margins of Precambrian basins in Northern Australia, parts of which remain un- or under-explored.

A common ontology for stable isotope data - Nina Welti; Steph Hawkins; Kathryn Waltenberg; Cath Hughes; Jagoda Crawford; Yanfeng Shu; Regina Campbell; Alex Leslie; Athina Puccini; Christoph Gerber; Axel Suckow; Geoff Fraser; et al. (Applied Geochemistry, 2026)

Invasive plant management in eastern North American Forests: A systematic review - Lauren S. Pile Knapp; David R. Coyle; Daniel C. Dey; Jacob S. Fraser; Todd Hutchinson; Michael A. Jenkins; Christel C. Kern; Benjamin O. Knapp; Dacoda Maddox; Cornelia Pinchot; G. Geoff Wang (Forest Ecology and Management, 2023)

Haemodynamic Effect of Left Atrial and Left Ventricular Cannulation with a Rapid Speed Modulated Rotary Blood Pump During Rest and Exercise: Investigation in a Numerical Cardiorespiratory Model - Eric L. Wu; Libera Fresiello; Matthias Kleinhyer; Bart Meyns; John F. Fraser; Geoff Tansley; Shaun D. Gregory (Cardiovascular Engineering and Technology, 2020)

Age constraints on the hydrothermal history of the Prominent Hill iron oxide copper-gold deposit, South Australia - Bryan Bowden; Geoff Fraser; Garry J Davidson; Sebastien Meffre; Roger Skirrow; Stuart Bull; Jay Thompson (Mineralium Deposita, 2017)

The Nolans Bore rare-earth element-phosphorus-uranium mineral system: geology, origin and post-depositional modifications - David L. Huston; Roland Maas; Andrew Cross; Kelvin J. Hussey; Terrence P. Mernagh; Geoff Fraser; David C. Champion (Mineralium Deposita, 2016)

Evaluation of Physiological Control Systems for Rotary Left Ventricular Assist Devices: An In-Vitro Study - Jo P. Pauls; Michael C. Stevens; Nicole Bartnikowski; John F. Fraser; Shaun D. Gregory; Geoff Tansley (Annals of Biomedical Engineering, 2016)

In Vitro Comparison of Active and Passive Physiological Control Systems for Biventricular Assist Devices - Jo P. Pauls; Michael C. Stevens; Emma Schummy; Geoff Tansley; John F. Fraser; Daniel Timms; Shaun D. Gregory (Annals of Biomedical Engineering, 2016)

Analysis of Low Molecular Weight Metabolites in Tea Using Mass Spectrometry-Based Analytical Methods - Karl Fraser; Scott J. Harrison; Geoff A. Lane; Don E. Otter; Yacine Hemar; Siew-Young Quek; Susanne Rasmussen (Critical Reviews in Food Science and Nutrition, 2014)

Lode–gold mineralization in the Tanami region, northern Australia - David L. Huston; Leon Vandenberg; Andrew S. Wygralak; Terrence P. Mernagh; Leon Bagas; Andrew Crispe; Alexis Lambeck; Andrew Cross; Geoff Fraser; Nick Williams; Kurt Worden; Tony Meixner; et al. (Mineralium Deposita, 2007)

Variation of Proanthocyanidins in Lotus Species - Subathira Sivakumaran; William Rumball; Geoff A. Lane; Karl Fraser; Lai Y. Foo; Min Yu; Lucy P. Meagher (Journal of Chemical Ecology, 2006)